Potential effect of household contact management on childhood tuberculosis: a mathematical modelling study - Peter J Dodd, PhD; Courtney M Yuen, PhD; Mercedes C Becerra, ProfPhD; Paul Revill, MSc; Helen E Jenkins, PhD; James A Seddon, PhD (Elsevier, 2018)
Summary: Background: Tuberculosis is recognised as a major cause of morbidity and mortality in children, with most cases in children going undiagnosed and resulting in poor outcomes. Household contact management, which aims to identify children with active tuberculosis and to provide preventive therapy for those with HIV or those younger than 5 years, has long been recommended but has very poor coverage globally. New guidelines include widespread provision of preventive therapy to children with a positive tuberculin skin test (TST) who are older than 5 years. Methods: In this mathematical modelling study, we provide the first global and national estimates of the impact of moving from zero to full coverage of household contact management (with and without preventive therapy for TST-positive children older than 5 years). We assembled data on tuberculosis notifications, household structure, household contact co-prevalence of tuberculosis disease and infection, the efficacy of preventive therapy, and the natural history of childhood tuberculosis. We used a model to estimate households visited, children screened, and treatment courses given for active and latent tuberculosis. We calculated the numbers of tuberculosis cases, deaths, and life-years lost because of tuberculosis for each intervention scenario and country. Findings: We estimated that full implementation of household contact management would prevent 159 500 (75% uncertainty interval [UI] 147 000-170 900) cases of tuberculosis and 108 400 (75% UI 98 800-116 700) deaths in children younger than 15 years (representing the loss of 7 305 000 [75% UI 6 663 000-7 874 000] life-years). We estimated that preventing one child death from tuberculosis would require visiting 48 households, screening 77 children, giving 48 preventive therapy courses, and giving two tuberculosis treatments versus no household contact management. Interpretation: Household contact management could substantially reduce childhood disease and death caused by tuberculosis globally. Funding and research to optimise its implementation should be prioritised. Funding: UK Medical Research Council, US National Institutes of Health, Fulbright Commission, Janssen Global Public Health.